López, A., Marrades, A. y González, J. (2023). La pugna por el nuevo orden mundial. Espasa, 356 pp. - Caballero Fernandez, Carles (Relaciones Internacionales, 2025)
Reseña de: López, A., Marrades, A. y González, J. (2023). La pugna por el nuevo orden mundial. Espasa, 356 pp.